Development of animals ecology module for macrozoobentos community at higher institution - Setyoko Setyoko; Fatchur Rohman; Hadi Suwono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Development of animal ecology module with a material of macrozoobenthos community in higher education aimed to develop teaching materials based on the needs of students of Biology Education. The study was conducted from January to March 2014. This research is a development research of module material. Module development is based on study results at the stage of Structure of Macrozoobenthos Community in the Mangrove area of Bukit Batu Beach of Bengkalis Regency. Research and development of animal ecology module are conducted by following 4D model steps. The results of module material development of macrozoobenthos community are used as teaching materials of animal ecology at Biology Education Dept., FTTE- Islamic University of Riau. Results of animal ecology module development obtained was based on expert validation of animal ecology material expert, teaching material, and field practitioners which amounted to 92.59%, 94.86%, and 92.4%, respectively with qualification of excellent and unnecessary to be revised. A test result of small group which was conducted by 30 respondents of students of Biology education, FTTE- Islamic University of Riau amounted to 78.4% with qualification of good and unnecessary to be revised. Module of animal ecology can be used as proper teaching materials by Biology Education student.